PERAN PEMERINTAH KOTA PEKANBARU UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM MENGURANGI SAMPAH DI KECAMATAN MARPOYAN DAMAI TAHUN 2023 - Putri, Aisyah Fadila; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The government plays a very important role in increasing community participation in waste reduction. As a regulator, the government is responsible for formulating policies that support sustainable waste management. As a dynamizer, the government plays a role in encouraging community involvement through socialization and education. Meanwhile, as a facilitator, the government must ensure the availability of adequate facilities and infrastructure to support the waste management system. This study aims to analyze the extent of the government's role in increasing community participation in waste management in Marpoyan Damai District, Pekanbaru City. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation studies. The results of the study show that the government has issued various policies, such as Regional Regulation No. 18 of 2008 concerning Waste Management and Pekanbaru Mayor Regulation No. 6 of 2023 concerning the Reduction of Plastic Bag Use. However, in its implementation, there are still various obstacles, such as a lack of policy socialization and low public awareness of sorting and managing waste. As a facilitator, the government has implemented various programs, such as awareness campaigns on reducing plastic waste, waste bank programs, awareness campaigns on reusing used items, awareness campaigns on Eco Enzymes, and others. However, public participation remains suboptimal due to insufficient education and lack of coordination with private sector entities and environmental communities. As a facilitator, the government has provided waste management facilities; however, in terms of reduction, these are still inadequate and do not fully meet community needs. Therefore, more innovative and collaborative strategies, as well as enhanced supervision and awareness campaigns, are needed to ensure that existing policies are implemented more effectively and encourage the community to be more active in waste reduction. The conclusion of this study is that the government's role in increasing community participation is still not optimal, as seen from the facilitator indicator. Keywords: The role of government, Community participation, Waste